Injection moulding simulation of wood–filled polypropylene thin-walled composite parts - Md Deros, Mohd Azaman (2015)
Currently, many industries are moving towards the production of products that exhibit properties, such as small thickness, low weight, small dimensionality, and environmental friendliness. In this project, a shallow thin-walled part (thickness = 0.7 mm) was designed to investigate wood-filled polymer composites in terms of the processability and quality of moulding parts. Numerical simulation (MoldFlow software) assisted with the Taguchi method,signal-to-noise (S/N) ratio and analysis of variance (ANOVA) was carried out in this research. This study focused on the in-cavity residual stresses, volumetric shrinkage and warpage behaviour associated with the thin-walled moulded part using different types of wood-filled polymer composites (PP + 40 %wt wood,PP + 50 %wt wood, and PP + 60 %wt wood). The analysis demonstrated that the shallow thin-walled part is preferable for moulding the wood-filled polymer composite material due to the low residual stress (i.e. centre of the part surface, 15-23 MPa) and warpage (0.02-0.42 mm) measured than flat thinwalled parts. The material PP + 60 %wt wood is not suitable for moulded thinwalled parts because of the early solidification (short shot) and the statistical results with a percentage contribution of residual error that was higher than the moulding parameters. However, the material PP + 50 %wt wood is the preferred type of wood-filled polymer composite for moulded thin-walled parts. The predicted in-cavity residual stresses for PP + 50 wt% wood are approximately 20.10 MPa, which is lower than the values of approximately 20.60 MPa and 31.10 MPa predicted for PP + 40 wt% wood and PP + 60 wt% wood, respectively. The differences in value of the contour-pattern distribution for PP + 50 wt% wood are small (in the ranges of -0.709 % to -0.174 %) compared to those for the other types of wood-filled polymer composites. The research revealed that the packing pressure and mould temperature are important parameters to reduce the residual stresses and volumetric shrinkage. To reduce warpage, the important processing parameters are the packing pressure, packing time and cooling time for moulded thin-walled part using wood-filled polymer composites. The in-cavity residual stress results indicated that the stress variation across the thickness exhibits a high tensile stress at the part surface, which changes to a low tensile stress peak value close to thesurface, with the core region experiencing a parabolic tensile stress peak. The volumetric shrinkage was lower near the gate than at the end-of-fill location along the flow path. The results also indicated that the volumetric shrinkage correlates with the warpage measured on the moulded part. The optimum parameter ranges for obtaining the minimum in-cavity residual stresses,volumetric shrinkage and warpages are as follows: a mould temperature of 40- 45 °C, a cooling time of 20-30 sec, a packing pressure of 0.85Pinject, and a packing time of 15-20 sec. The melt flow index (MFI) is inversely proportional to the residual stress, volumetric shrinkage and warpage formation on the moulded thin-walled part. The value of the melt flow index must be considered in injecting wood-filled polymer composites rather than making the selection based on the filler loading content. Visualisation of the simulation results shows that the minimum warpage distribution appears more uniform for the moulded thin-walled part using PP + 50 wt% wood than for that using PP + 10 wt% glass fibre and PP. The warpage at the midpoint of the part surface injected using PP + 50 wt% wood is 0.04mm lower than that value of 0.08mm using PP + 10 wt% glass fibre. This phenomenon can be attributed to changes in the distribution of residual stresses that occur in the core regions: PP + 50 wt% wood is 15.77MPa lower than PP + 10wt% glass fibre (17.17MPa). Furthermore, the volumetric shrinkages of PP + 10 wt% of glass fibre are observed to begin to become uniform at 3.95% from 2.3 sec, which is faster than that of PP + 50 wt% wood at 2.23% from 2.5 sec take longer or more time. More time required for the solidification process tends to minimise warpages occurring at the regions.